Application of orbital sensors to detect deforestation in the Amazon rainforest - Silva, Cláudia Arantes (2021)
Tese (doutorado) — Universidade de Brasília, Instituto de Geociências, Pós-Graduação em Geociências Aplicadas, 2021.